Urban food retail in Africa: The case of Addis Ababa, Ethiopia - Woldu, Thomas; Abebe, Girum; Lamoot, Indra; Minten, Bart (International Food Policy Research Institute, 2013)
We study food retail in Addis Ababa, one of the biggest cities in Africa. Based on a primary survey of food retail outlets selling cereals, fruits and vegetables, and processed foods, we note high variation in quality and prices in the city and an increasing differentiation in food retail markets in recent years. On the high-end, we see the emergence of domestic (as foreign direct investment in retail is not allowed) private modern retail outlets that deliver high quality products at high prices and that focus mostly on wealthier areas and consumers. At the other side, we see cooperative retail that delivers food at controlled and subsidized prices. The latter shops are characterized by typical price control policy problems, reflected in regular lack of supplies and queuing. It seems that food retail markets would be improved by stimulating the emergence of a competitive private retail sector, the abolishment of price controls, and targeted subsidies or safety nets for the poor.